Harmony of Islam and Local Traditions in Indonesia: Challenges and Opportunities in the Era of Modernization - Mohammad Abdul Al Halib; Lina Pusvisasari (al-Wadhih: Journal of Islamic History and Civilization, 2025)
Islam in Indonesia has a unique characteristic reflected in its integration with local traditions. This relationship has been established since the early arrival of Islam in the archipelago, shaping an inclusive and distinctive Islamic identity. However, in the era of modernization and globalization, the harmony between Islam and local traditions faces significant challenges, including cultural erosion, polarization among Islamic groups, and the emergence of extreme views rejecting local traditions. This study aims to examine the dynamics of the relationship between Islam and local traditions in Indonesia, focusing on the challenges posed by modernization and the opportunities to maintain this harmony. The approach utilized includes historical and sociological analysis, with case studies of local Islamic traditions such as Maulid Nabi, tahlilan, and Grebeg Maulud. The findings reveal that local traditions not only serve as a means of cultural preservation but also as an effective medium for Islamic propagation. Nevertheless, modernization has significantly influenced younger generations, who tend to abandon local traditions. On the other hand, social media and information technology present opportunities to strengthen the harmony between Islam and local traditions when utilized wisely. This study emphasizes the importance of dialogue among Islamic groups and the preservation of local traditions as an integral part of national identity. With an inclusive approach, Islam and local traditions can continue to coexist, contributing positively to Indonesia's cultural diversity amidst global challenges.